Developing and validating entrustable professional activities for neurology residency training programs in Saudi Arabia: a modified Delphi study - Alkhotani, Amal M.; Tawakul, Abdullah; Alharbi, Laila A.; Alotaibi, Manal E.; Samannodi, Mohammed S.; Alim, Hussam M.; Khadawardi, Hadeel A.; Almalki, Fahd; Imam, Ahmad A.; Dairi, Mohammad S.; Turkistani, Yosra A.; Bulkhi, Adeeb A.; et al. (Frontiers in Neurology, 2025)
Background and objectiveEntrustable professional activities (EPAs) are tasks that medical professionals can be entrusted to perform in unsupervised settings once they have achieved sufficient specific competencies. Despite their importance, nationally validated neurology EPAs are lacking in Saudi Arabia. This study aimed to develop and validate neurology EPAs in Saudi Arabia.MethodsA list of neurology EPAs was developed after an extensive review of existing neurology training program competencies and EPAs. Neurology experts were invited to participate in two rounds of a modified Delphi technique to review the list of EPAs and assess their relevance and representativeness using a 5-point Likert scale. In total, 21 neurologists participated in the study. Descriptive statistics were used to describe participants’ demographic characteristics and group responses to each EPA. Cronbach’s alpha was used to assess the internal consistency of the responses across both Delphi rounds.ResultsIn the first round, 26 EPAs were validated, 10 were excluded owing to a lack of relevance, and one EPA was added as a modification of the existing items. In the second round, one more EPA was excluded because of a lack of relevance, resulting in a final set of 25 neurology EPAs.ConclusionThis study developed and content-validated a set of EPAs for neurology residency training in Saudi Arabia. It represents an initial step toward implementing an EPA-based curriculum. Further steps are necessary to ensure adequate integration into training programs.